Rodovias em áreas urbanizadas e seus impactos na percepção dos pedestres - Silva Junior, Sílvio Barbosa da (Universidade Federal de São Carlos, 2006)
This work presents the results of a opinion poll, applied to the inhabitants of an urban area along the BR-050 highway, in Uberlândia MG, carried out to estimate the importance of the impacts originated by the Barrier Effect and its characterization attributes. The Barrier Effect refers to the motorized transportation infrastructure impacts over the non-motorized transport. The method applied to this survey to determine the importance degree of each variable and its attributes of characterization related to the Barrier effect consists of a questionnaire, elaborated according to the Likert recommendations, and with the utilization of the Successive Intervals Method to determine the distance of the elements of a scale. The method which has been considered appropriate and easy to apply, produced satisfactory elements to the proposed analysis. The results show that the highway, inserted in a urban site, limitate the on foot transport for the inhabitants of the surroundings of the highway (effects), resultants of the Barrier Effect. It also was possible to identify the importance of defining attributes of each limitation (causes).
Keywords: Planejamento urbano; Rodovias; Cidades; Pedestres; Barrier effect; Attributes; Variables; Highway; On foot transport; ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES::RODOVIAS; PROJETO E CONSTRUCAO